Gastropod Density and Diversity in the Mangrove Forest of Pagatan Besar Village, Tanah Laut Regency, Indonesia - Bimo Aji Nugroho; Mochamad Arief Soendjoto; Muhammad Zaini (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
Public awareness and knowledge on mangrove forest biodiversity, especially gastropods, is very limited. This study aims to compare the density and diversity index of gastropod species according to their distance from the coastline and to analyze the relationship of the two with the physical environment around them. Three lanes were placed in the southern part of the mangrove forest. The first lane (LT-1) was placed about 5 m from the coastline towards the sea. The second lane (LT-2) was placed 10 m towards the sea from LT-1 and the third lane (LT-3) was 10 m from LT-2 towards the sea. In each lane there were 10 (1 mx 1 m) plots and the distance between adjacent plots was 10 m. A total of 1.432 Gastropod individuals consisting of 16 species and 7 families were collected from 30 plots. In detail 16 species (927 individuals) were collected from LT-1, 16 species (500 indv) from LT-2, and only 3 species or 5 individuals from LT-3. The density of LT-1, LT-2, and LT-3 species respectively was 92.7; 50.0; and 0.5 indv.m-2, while the diversity index successively was 2.56 (moderate); 2.53 (moderate); and 0.95 (low). Both species density and diversity in lanes that are close to the coastline are higher than in lanes located in the direction of the sea. The base substrate on the path that was close to the coastline was clay, while on the lane that laid in the direction of the sea was sandy loam.